2004
DOI: 10.1111/j.1460-9568.2004.03563.x
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the retinoid signalling pathway causes a deposition of amyloid β in the adult rat brain

Abstract: We have disrupted the retinoid signalling pathway in adult rats by a dietary deficiency of vitamin A. After 1 year of this dietary deficiency, there was a deposition of amyloid beta in the cerebral blood vessels. There is a downregulation of retinoic acid receptor alpha in the forebrain neurons of the retinoid-deficient rats and a loss of choline acetyl transferase expression, which precedes amyloid beta deposition. In neocortex of pathology samples of patients with Alzheimer's disease, the same retinoic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
131
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(138 citation statements)
references
References 53 publications
6
131
0
1
Order By: Relevance
“…Furthermore, these post-natal effects of experimental retinoid manipulations incur minimal anatomical changes (in comparison to manipulations during the prenatal period) whereas behavioral effects are quite profound. Intriguingly, the cortex of retinoic acid deprived rats is characterized by beta-amyloid accumulation and other changes that parallel those in Alzheimer' disease [83]. Additionally, normal memory loss in aging rats can be alleviated by vitamin A therapy [84].…”
Section: Retinoids and Cd38mentioning
confidence: 99%
“…Furthermore, these post-natal effects of experimental retinoid manipulations incur minimal anatomical changes (in comparison to manipulations during the prenatal period) whereas behavioral effects are quite profound. Intriguingly, the cortex of retinoic acid deprived rats is characterized by beta-amyloid accumulation and other changes that parallel those in Alzheimer' disease [83]. Additionally, normal memory loss in aging rats can be alleviated by vitamin A therapy [84].…”
Section: Retinoids and Cd38mentioning
confidence: 99%
“…Il a ete montre que l'hypoactivite de la voie de signalisation des retinoïdes entraîne la formation anormale et le depôt des petides Ab (Corcoran et al, 2004). Ceci a en particulier ete montre chez des rats carences en vitamine A. Apres consommation pendant 1 an d'une alimentation totalement depourvue de cette vitamine, les animaux presentaient une hypoactivation de la voie de signalisation de la vitamine A, et avaient developpe des depots b-amyloïdes dans leur cerveau.…”
Section: Vitamine a Et Maladie D'alzheimerunclassified
“…Retinoid receptors are preferentially located in structures involved in cognition (cerebral cortex, amygdala, hypothalamus, hippocampus and striatum), and there is evidence that they participate in synaptic plasticity as well as in learning and memory processing (Lane and Bailey 2005). Accordingly, several studies have already demonstrated that disruption of retinoid signaling pathways is directly implicated in the pathophysiology of Alzheimer's disease, namely in the amyloidogenic pathway (Misner et al 2001;Husson et al 2006;Corcoran et al 2004). Whether obesity-related adipocyte dysfunction contributes to this central retinoid disruption remains unclear.…”
Section: Visfatin and Rbp-4mentioning
confidence: 99%